Implementation of Curriculum Development: Case Study on Early Childhood Education Teachers in Sragen Regency - Nurlia Yusniar; Slamet Slamet; Widya Novi Angga Dewi; Mohammad Bisri (Universitas of Muhammadiyah Makassar, 2022)
This study examines the implementation of early childhood education curriculum development in rural areas by early childhood education teachers in Sragen Regency. The research aims to place teachers as facilitators in school changes based on their perceptions of implementation as a result of developing the Early Childhood Education curriculum that the Regional and Central Government continuously develops. This study used a qualitative design with a case study approach. The informants of this research were ten early childhood education teachers in rural and urban areas of Sragen Regency, where the key informants were policymakers, namely the Head of the Education and Culture Office of Sragen Regency. The study results illustrate the advantages and disadvantages of competency-based curriculum implementation based on the experience of each according to the location of the teacher where he teaches. It is also implied that effective curriculum implementation is something or information conveyed by the teacher to students when the learning process takes place. Such conditions did not run smoothly, but there were many challenges, especially for teachers in rural areas. Apart from the problem of implementing the curriculum, facilities and infrastructure, there is also a lack of funding and inadequate human resources. It is recommended that future policymakers, teacher attention, and parental involvement could employ these findings for a decision basis. It is also suggested that policymakers could prioritize educational arrangements in complex Early Childhood Education before curriculum planning and implementation. The importance of involving teachers in rural areas can accommodate the aspirations of local wisdom and cultural behaviour as a characteristic of a plural nation-state.Penelitian ini mengkaji penerapan pengembangan kurikulum PAUD di pedesaan oleh guru PAUD di Kabupaten Sragen. Penelitian bertujuan untuk menempatkan guru sebagai fasilatator dalam perubahan di sekolah dengan mendasarkan pada persepsinya dalam pengimplementasian sebagai hasil pengembangan kurikulum di kelembagaan PAUD yang terus dikembangkan oleh Pemerintah Daerah dan Pusat. Studi ini digunakan desain kualitatif, ada 10 guru PAUD di pedesaan dan perkotaan wilayah Kabupaten Sragen sebagai informan, selain informan kunci adalah pemangku kebijakan yaitu Kepala Dinas Pendidikan dan Kebudayaan Kabupaten Sragen. Hasil penelitian menggambarkan bahwa ada kelebihan dan kelemahan dari penerapan kurikulum berbasis kompetensi yang didasarkan pada pengalaman masing-masing sesuai lokasi guru tempat mengajar. Tersirat juga bahwa implementasi kurikulum yang efektif adalah instruksi guru kepada peserta didik ketika proses pembelajaran berlangsung. Perspektif seperti itu juga banyak memberikan wawasan bahwa tantangan yang dialami oleh guru PAUD di pedesaan selain dalam implementasi kurikulum juga sarana dan prasarana yang kurang memadai, selain juga kekurangan sumber dana dan sumber daya manusia. Hasil penelitian merekomendasikan bahwa temuan penelitian ini dapat digunakan sebagai dasar untuk pemangku kebijakan di masa depan, perhatian guru, dan orang tua, bahkan ditegaskan bahwa pengaturan pendidikan di PAUD yang kompleks harus diperioritaskan oleh pembuat kebijakan sebelum perencanaan dan penerapan kurikulum, yang melibatkan guru PAUD di pedesaan sehingga kearifan lokal dan budaya perilaku sebagai ciri negara bangsa yang plural dapat terwadai.